Hubungan Konsumsi Makanan Jajanan dengan Kejadian Diare pada Anak Sekolah di Surabaya - Berliandita Shabhati; Annis Catur Adi (Universitas Airlangga, 2023)
Background: Gastrointestinal infections that are still found in the surrounding environment are diarrhea. Diarrhea can be affected by various factors, one of them is the consumption of snack foods that the safety is not guaranteed. Snacks are one of the foods that are often consumed by students. Until now, there are still many snacks that contain contaminants that can cause a disease Objectives: This research aims to identify the correlation between the consumption of snacks and the incidence of diarrhea in elementary school students. Methods: This research used a quantitative methods. This type of research was an observational study used cross sectional research design. Sampling in this study used a purposive random sampling technique which then obtained a total sample of 72 respondents. The data obtained in this study were analyzed using the bivariate analysis method, namely Spearman's rank.. Results: The results of this study found that most of the respondents had moderate consumption of snacks (66,7%). The respondents who experienced diarrhea amounted to 22.2%.. The results of the research based on data analysis shows that there is a correlation between snacks consumption and the incidence of diarrhea in primary school students with a p-value of 0.03 (<α = 0.05). Conclusions: There is correlation between snack consumption and diarrhea incidences in elementary school students.